Evaluation of the Appearance of Cardiomegaly on Chest Films of Pediatric Patients with Acute Poststreptococcal Glomerulonephritis - Husein Albar; Syarifuddin Rauf; Azis Tanra (Paediatrica Indonesiana, 1999)
We evaluated 17 patients with acute poststreptococcal glomerulonephritis (ASPGN) hospitalized in nephrology ward of Wahidin Sudirohusodo Hospital Ujung Pandang. The initial chest films and echocardiograms demonstrated the presence of cardiomegaly and pericardial effusion, respectively. Seven days later, either the cardiomegaly or the pericardial effusion disappeared. According to the statistical analysis, the relationship between the occurrence of cardiomegaly and pericardial effusion was significant (p<0.001). From this study we conclude that the occurrence of cardiomegaly in patients with ASPGN seems to be due to pericardial effusion. Our findings need to be confirmed by studying a larger number of patients.